Bank Syariah Indonesia dalam Menguatkan Ekonomi Sektor UMKM pada Masa Pandemi: Indonesian Sharia Bank in Strengthening Economy of the UMKM Sector During Pandemic - Latifah, Eny; Abadiyah, Fajriyatul; Muawanah, Rifatul; Sukma, Diniyah (Indonesian Journal of Islamic Economics and Finance, 2021)
This study aims to find out the role of the Indonesian Islamic Bank merger in strengthening the economy in the MSME sector during the pandemic. The research method used is descriptive qualitative research with the type of library research, searching and recording data from various sources that are still related to the topic of the problem so that it becomes a unified whole to conclude. The results showed that the merger of Indonesian Sharia Banks had an important role in strengthening the economy in the MSME sector during the pandemic, namely BSI collaborated with LAZ Bangun Sejahtera Mitra Ummah to create an ISDP Program for entrepreneurial students in the form of providing UKT scholarships, coaching, mentoring, intensive and programmed training. In addition, BSI also collaborates with the well-known e-commerce platform Shopee in the Go Digital MSME program, which is expected by millennial entrepreneurs not only to make varied products at low prices but also to create the best quality brands and be able to take advantage of the development of digital technology for transformation business to the global market (go digital go international).